Continuous Proximal Monitoring of Diameter Variation from Root to Fruit - Arash Khosravi; Enrico Maria Lodolini; Veronica Giorgi; Francesco Belluccini; Adriano Mancini; Davide Neri (Horticulturae)
Proximal plant-based monitoring provides high-resolution data about trees, leading to more precise orchard management and in-depth knowledge about tree physiology. The present work focuses on continuous real-time monitoring of olive cv. ‘Ascolana tenera’ over hourly intervals during the third stage of fruit growth (mesocarp cell expansion) under mild water stress conditions (ψStem above −2 MPa). This is achieved by mounting dendrometers on the root, trunk, branch, and fruit to assess and model the behavior of each organ. The diameter variation in each organ over different time intervals (daily, two-weeks, and throughout the entire experiment), as well as their hysteretic patterns relative to each other and vapor pressure deficit, are demonstrated. The results show different correlations between various organs, ranging from very weak to strongly positive. However, the trend of fruit versus root consistently shows a strong positive relationship throughout the entire experiment (R2 = 0.83) and a good one across various two-week intervals (R2 ranging from 0.54 to 0.93). Additionally, different time lags in dehydration and rehydration between organs were observed, suggesting that the branch is the most reactive organ, regulating dehydration and rehydration in the tree. Regarding the hysteretic pattern, different rotational patterns and characteristics (shape) were observed among the organs and in relation to vapor pressure deficit. This research provides valuable insight into flow dynamics within a tree, models plant water relations and time lags in terms of water storage and transport, and could be implemented for precise olive tree water status detection.